Identifying priorities for the joint conservation of maritime built heritage and marine biodiversity: An assessment of shoreline engineering on the Isles of Scilly, UK, using historical datasets - Baxter, T; Coombes, M; Viles, H (Elsevier, 2022)
Growing concern over the ecological impact of maritime structures has led to increasing attempts to quantify the extent of marine human development. However, maritime heritage assets (i.e., historic structures of cultural significance, such as decommissioned quays) are often missing in these assessments as many of these structures are not recorded in conventional datasets of maritime infrastructure, instead featuring exclusively in heritage registers. At the same time, heritage assets may provide unintentional ecological benefits to marine wildlife due to their age, traditional construction, and protected status, and as such, comprehensive assessments of marine human development cannot be achieved without the inclusion of historical data. Using the Isles of Scilly as a geographically confined case study, we present a novel methodology for quantifying the full extent of marine engineering structures (including heritage assets) at a regional scale, and for identifying priority structures for joint biodiversity and heritage conservation.